EMPOWERMENT KEPALA RUANGAN TERHADAP KOMPETENSI PERAWAT PELAKSANA DI RUMAH SAKIT : SYSTEMATIC REVIEW - Astuty, Mazly; Hariyati, Rr. Tutik Sri; Nuraini, Tuti; Sekarsari, Rita (Menara Medika, 2025)
Abstract Backgound: Nurse competence can be influenced by the empowerment of head nurse. Empowerment is how head nurse conditions the climate and work culture in the nursing ward that can improve nurse competences. The existing literature is still very varied, therefore a systematic review is needed to determine the specific empowerment carried out by the head nurse based on published scientific evidence.Purpose: The study was aimed to know how the empowerment of head nurse affected nursing staff competences in the hospitalMethods: Conducted a systematic review of the literature from 2013 to 2023. Data were collected from 6 databases (EMBASE, EBSCOHost, Sage Journals, ScienceDirect, Scopus, and PubMed), using the keywords “empowerment”, “empowerment of head nurses”, and “empowerment AND head nurses”. The literature study was limited to English-language, as well as literature that had abstracts and full text. The systematic review was organized using PRISMA. The quality of the articles was assessed using JBI critical appraisal tools.Results: There were 8 articles included in the review category. The results showed that there are four actions of the head nurse to empower the staff, including: 1) providing training to increase skills and knowledge, 2) providing autonomy, 3) being open, communicative and caring, and 4) being a shelter.Conclusion: The head nurse played an important role in managing the ward by setting policies to coordinate nursing staff tasks, and solve problems with the staff. Empowerment can improve the organization climate and culture to sharpen the quality of nursing care.Keywords: empowerment, head nurse, nursing staff, systematic review Abstrak Latar belakang: Kompetensi perawat dapat dipengaruhi oleh beberapa factor, salah satunya dalah empowerment dari kepala ruangan. Empowerment yang dimaksud dalam hal ini adalah bagaimana kepala ruangan mengkondsikan iklim dan budaya kerja di ruangan yang dapat meningkatkan kompetensi perawat. Literatur yang ada tentang topik ini masih sangat bervasiasi, oleh karenanya dibutuhkan sistematik review untuk mengetahui empowerment yang spesifik dilakukan kepala ruangan berdasarkan bukti-bukti ilmiah yang telah dipublikasikan.Tujuan: Untuk mengetahui bagaimana empowerment kepala ruangan dalam mempengaruhi kompetensi perawat pelaksana di rumah sakit.Metode: Melakukan tinjauan literatur secara sistematis dari tahun 2013 sampai dengan 2023. Data dikumpulkan dari 6 database (EMBASE, EBSCOHost, Sage Journals, ScienceDirect, Scopus, dan PubMed), dengan menggunakan kata kunci empowerment, empowerment of head nurse, dan empowerment AND head nurse. Studi literatur terbatas hanya pada literatur yang berbahasa Inggris, serta literatur yang memiliki abstrak dan full text. Sistematik review disusun dengan menggunakan PRISMA. Kualitas artikel yang dihasilkan dinilai dengan menggunakan JBI critical appraisal tools.Hasil: Terdapat 8 artikel yang masuk kedalam kategori review. Hasil review menunjukkan terdapat empat tindakan kepala ruangan untuk memberdayakan staf perawat, antara lain: 1) memberikan pelatihan untuk menambah skill dan pengetahuan, 2) memberikan otonomi, 3) bersikap terbuka, komunikatif dan caring, dan 4) menjadi tempat bernaung bagi perawat dalam bekerja.Kesimpulan: Kepala ruangan berperan penting dalam mengelola unit ruangan dengan menetapkan kebijakan untuk mengkordinasikan tugas dari staf perawat, dan bersama-sama dengan staf perawat memecahkan masalah. Empowerment yang dilakukan kepala ruangan terhadap staf perawat dapat meningkatkan iklim dan budaya organisasi untuk mempertajam kualitas asuhan pelayanan keperawatan.Kata Kunci: empowerment, kepala ruangan, perawat, systematic review